Understanding how digital transformation can enable SMEs to achieve sustainable development: A systematic literature review - Simon Philbin; Radhakrishnan Viswanathan; Arnesh Telukdarie (Small Business International Review)
Small and medium-sized enterprises (SMEs) are key drivers of economic growth and development. Innovation through digital transformation has the capacity to enable sustainability, competitiveness and customisation in products and services. However, adoption of digital technologies by SMEs to underpin sustainability outcomes is poorly understood. A systematic literature review identified an initial dataset of 1300 articles, which after screening and application of exclusion criteria resulted in a dataset of 64 articles for synthesis. Analysis was carried out according to three main areas, namely the technology aspects of digital transformation, sustainable development according to the triple bottom line (i.e. economic, environmental and social aspects), and the business characteristics of SMEs. In the latter case, business strategy and management, organizational structure, organizational culture, skills and qualifications, and leadership factors are identified from the literature. Furthermore, literature expressing the triple bottom line dimensions and the type of Industry 4.0 technology areas adopted are synthesized. Correlation of the data through bibliographic analysis is provided on the type of technology enabling SMEs towards a pathway for sustainable development as well as synthesis of future research directions arising from the study.